Antimicrobial susceptibility pattern of urinary tract pathogens - Khameneh Zakieh (Saudi Journal of Kidney Diseases and Transplantation, 2009)
Microbial drug resistance is a major problem in the treatment of infectious diseases worldwide. The purpose of this survey is to determine the prevalence of the type of bacterial agents that cause urinary infection and to assess the antimicrobial sensitivity pattern in the Urmia Medical University, Iran. In the period between 2005 and 2006, urine cultures collected were analyzed. Positive culture was defined as growth of a single bacterial species with colony count of > 100,000 CFU/mL. Stratification was done according to age-group and gender. Statistical tests used included chi-square to evaluate differences between susceptibility rates. A total of 803 urine culture positive patients were studied of whom 81.6% were females and 18.4% were males. The common micro-organisms isolated were E. coli (78.58%), Klebsiella (5.48%), Proteus and Staphylococcus. About 89% of the E. coli isolated showed sensitivity to cephtizoxin, 83.9% to gentamycin and 83.2% to ciprofloxacin; the highest resistance was shown to ampicillin and co-trimoxazole. Surveys of this nature will give a clear idea about the bacteriologic profile in a given institution as well their antibiotic sensitivity profile. This will act as a guide to commencing empirical antibiotic treatment in patients with urinary infections until such time culture reports are available.